Los recursos didácticos y su incidencia en el aprendizaje significativo en lengua y literatura de los estudiantes del décimo año de educación general básica del colegio de bachillerato 27 de Febrero de la ciudad de Loja, periodo académico 2013-2014 - Pogo Córdova, Elcio Marino (2015)
The present work of research called "THE TEACHING RESOURCES AND ITS INCIDENCE IN THE MEANINGFUL LEARNING IN LANGUAGE AND LITERATURE OF THE STUDENTS OF THE TENTH YEAR OF GENERAL EDUCATION BASIC COLLEGE FEBRUARY 27 OF THE CITY OF LOJA, ACADIE PERIOD 2013 – 2014”, was developed with the purpose of knowing the teaching resources used by the professors and their incidence in the meaningful learning in Language and Literature of the students of the tenth year of Basic General Education of the College February 27 of the city of Loja, academic period 2013-2014, for this we used the methods; scientific, analytic, synthetic, inductive and deductive, was also used techniques such as the bibliographic and the survey. A questionnaire as a tool of the research that was applied to seven teachers and seventy-one students of tenth year of Basic General Education. As a result it can be shown that the unique teaching and learning resources that teachers used to teach the classes are: the book of job and the chalkboard; these resources have been made that the students take the subject of one way tiresome, so the developed in the macrodestrezas is at least do not have any interest in reading, studying in a way only's calls to get a qualification and no significant learning. These resources used by teachers as are the book of Job and slate have not helped the students to achieve lasting programming, which makes it essential to use innovative teaching resources to support the educational work. It is recommended that you use different teaching and learning resources such as: books, audios, projectors, and mainly the different literary works that serve as supports to the workbook and assist the development of the programming for the students, encouraging to learn the subject interacting with these technological means